2018
DOI: 10.1134/s1607672918010076
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones Regulate the Expression of Nuclear Genes Encoding the Components of the Plastid Transcription Apparatus

Abstract: As multifunctional regulators of physiological processes, phytohormones play an important role in the regulation of expression of the plastid genome and chloroplast biogenesis. Hormones can directly regulate the expression of genes localized in the chloroplast genome. However, many components of the plastid transcription apparatus are encoded by nuclear rather than plastid genes. It remains obscure whether these nuclear genes are subject to hormonal regulation. This is the first study to show that phytohormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…In this context, a recent finding concerning the effects of phytohormones on the expression of nuclear genes of the plastid transcription machinery is noteworthy [42]. It was shown that ABA, MJ and SA decrease the expression of nuclear genes of the chloroplast transcription machinery, including sigma factors and PAPs [42], so their action results in a similar effect to that observed here for rps10 and aox1a: rpoTmp.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this context, a recent finding concerning the effects of phytohormones on the expression of nuclear genes of the plastid transcription machinery is noteworthy [42]. It was shown that ABA, MJ and SA decrease the expression of nuclear genes of the chloroplast transcription machinery, including sigma factors and PAPs [42], so their action results in a similar effect to that observed here for rps10 and aox1a: rpoTmp.…”
Section: Discussionsupporting
confidence: 74%
“…In this context, a recent finding concerning the effects of phytohormones on the expression of nuclear genes of the plastid transcription machinery is noteworthy [42]. It was shown that ABA, MJ and SA decrease the expression of nuclear genes of the chloroplast transcription machinery, including sigma factors and PAPs [42], so their action results in a similar effect to that observed here for rps10 and aox1a: rpoTmp. A significantly increased level of SA in rps10 leaf extracts (figure 8) supports the hypothesis that SA could act as a mediator in the signal transduction cascade from mitochondria to the nucleus to chloroplasts leading to a decline in the level of chloroplast transcription machinery components.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The same authors obtained similar results in barley leaves [53]. In line with this, Danilova et al [54] found that most of the nuclear genes that encode different plastid transcriptional machinery components, including RPOTp and RPOTmp, were down-regulated in Arabidopsis seedlings exposed to ABA. This repressive effect of ABA on plastid gene expression could be mediated by alarmone guanosine-30-50-bisdiphosphate (ppGpp), which accumulates in chloroplasts in response to abiotic stress, and to ABA, jasmonate or ethylene hormones [55,56].…”
Section: Discussionsupporting
confidence: 52%
“…ESPRESSO transcripts cycle in a diurnal pattern and LIGHT1 responds to various wavelengths and has a significant epistatic interaction with LIGHT2/PHYB . A separate transcript analysis revealed that PAP8 responds to temperature (Danilova et al , 2018a) and phyto‐hormones (Danilova et al , 2018b). In the following, PAP8 will be used as the gene name for At1g21600 also corresponding to ESPRESSO , LIGHT1 or pTAC6 .…”
Section: Introductionmentioning
confidence: 99%